Improving adaptability to competitive strain through comprehensive training for badminton players - Melnikova, T.I.; Kucherenko, Yu.O.; Vinogradova, O.P. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to investigate the potential of integrated training methods in improving badminton players’ adaptation to competitive stress. Methods and structure of the study. At the end of the main part of the session, the badminton players performed a set of integrated training exercises for 20-25 minutes. The assessment of the effectiveness of integrated training was based on indicators of physical, technical, functional and psychological fitness. Results and conclusions. The integrated stimuli of physical and technical exercises, which reflect the specific nature of competitive loads to the greatest extent, ensure the stability of badminton players’ technical actions. The use of integrated training methods during the competitive phase of preparation ensures high stability of the athletes’ physiological functions.